Assessment of pedigree information in the Quarter Horse: Population, breeding and genetic diversity - Faria, Ricardo António Silva [UNESP] (2018)
This study aimed to evaluate population parameters and to describe the genetic diversity of Quarter Horse breed (QH) in Brazil, reported for the first time in the literature. The pedigree data comprised 131,716 animals representing the total population (TP), with records of animals born between 1747 and 2008. The reference population (RP) representing the last generation was applied in this study considering 47,861 animals born between 2000 and 2008. The average generation interval was 9.6 and 10.8 years in TP and RP, respectively. The average equivalent complete generations (EG) were 5.09 (TP) and 6.24 (RP). The inbreeding coefficient (F), average relatedness (AR) and the increase in inbreeding by generation (ΔF) was 1.07%, 0.95% and 0.24%, respectively, for TP. The effective population size (Ne) based on ΔF was 195 and 164 for TP and RP, respectively. The effective number of founders (fe) was 1045 and 811 for TP and RP, respectively, that of ancestors (fa) was 156 and 113, and that of founder genomes (fg) was 105 and 66. The fe/fa and fe/fg ratios in TP were 6.70 and 9.95, respectively, and an increase was observed in RP, indicated a strong bottleneck effect. The total genetic diversity of the QH breed was explained by 4780 ancestors, with 50% of diversity being explained by only 121 and 72 ancestors in TP and RP, respectively. The thoroughbred stallion Three Bars is the most influential ancestor with the largest marginal genetic contribution for TP (5.73) and RP (5.94%). The results demonstrate a large number of founders and ancestors, but a small ancestor group was responsible for the continuity of the QH breed in Brazil. These finding highlight the importance of monitoring genetic diversity, including follow-up by breeding programs, to permit control of the next generations.